4CPS-207 Improving the safety of pharmacotherapy in paediatric haemato-oncology by clinical pharmacy services. (23rd March 2022) - Gradwohl, C; Pichler, H; Engstler, G; Nagele, F; Anditsch, M; Stemer, G
Abstract : Background and importance: Prevention of drug-related problems (DRP) beneficially affects patient outcomes. Children who are treated for haemato-oncological diseases or who are receiving a haematopoietic stem cell transplantation (HSCT) are highly susceptible to DRP. Paediatric clinical pharmacy services (CPS) showed a positive impact on several outcome measures including reduction of DRP. Aim and objectives: This evaluation aimed to assess the impact of CPS in a paediatric tertiary care centre specialising in haemato-oncology by quantifying DRP and pharmaceutical interventions (PI), determining their acceptance rate, rating their clinical significance and estimating economic benefit. Material and methods: From June until December 2020, a clinical pharmacist (CP) provided CPS, which included medication reviews and subsequent ward round participations (A: haemato-oncology, 11 beds; B: HSCT unit, 10 beds). The CP and an independent expert panel consisting of two clinical pharmacists and two paediatric haemato-oncologists assessed the PI for clinical significance. 1 Economic benefit was estimated retrospectively by drug therapy cost reductions and avoided follow-up costs based on prevention and management of adverse drug reactions (ADR). 2 Results: During 32 ward rounds, 230 DRP were addressed in 36 children (median age 7 (0.4–17) years). The acceptance rate for PI was 73.5%. The most common DRP concerned need for drug monitoring, need for information/therapy discussion and drug–drug interactions; the most common PI were drug-monitoring, drug-information and dose adjustments. The CP assessed 66% of PI as very significant or significant and correlation with the expert rating was significant (p≤0.0001). Costs of CPS were €7200. PI led to estimated drug therapy cost reductions of €5500. Prevention of 11 and identification of 24 ADR led to estimated avoided follow-up costs of €14 300–€27 500 and €31 200, respectively. Conclusion and relevance: This evaluation showed that CPS for a tertiary care centre specialising in paediatric haemato-oncology is capable of identifying and preventing DRP by clinically significant PI. The estimated economic benefit of CPS was at least six-fold higher than its costs. Based on the results, CPS were expanded in our hospital. References and/or acknowledgements: 1. Hatoum HAT, et al. Physicians' review of significant interventions by clinical pharmacists in inpatient care. Drug Intell Clin Pharm 1988;22 :980–982. 2. Zuba Martin AK. (2016) Evaluation Pilotprojekte 'Polypharmazie'. Gesundheit Österreich, Wien. Conflict of interest: No conflict of interest